Verification of Brachytherapy Sources Against Ir-192 HDR Using Well Type Ionization Detectors at Universitas Andalas Hospital - Ramacos Fardela; Rika Analia; Atika Maulida; Suci Ramda Rena; Fiqi Diyona; Dedi Mardiansyah (Lambung Mangkurat University Press, 2023)
The Radiotherapy Unit at Andalas University Hospital (Unand Hospital), Padang City, has a brachytherapy facility with multichannel indexer technology of High Dose Rate on the Remote after Loading System type MicroSelectron HDR and has 6 channels. The radioactive source used is Iridium-192 or Ir-192, with an initial activity of about 12 Ci. This study uses a well-type chamber ionization detector to verify the brachytherapy source against HDR Ir-192. The well-type chamber detector measures the radiation dose given to the patient during the brachytherapy procedure. This study uses detectors to measure radiation dose at several points around the source. The study was conducted by verifying the activity of the radiation source in Ir-192 brachytherapy using a voltage of 200 V and 400 V. It was regulated using an electrometer connected to a detector. The results show that the well-type chamber detector could accurately verify the source of brachytherapy. In addition, the measured activity values are in accordance with those permitted in standardization in brachytherapy, which is around 10 to 12 GBq. Therefore, well-type chamber ionization detectors can effectively verify brachytherapy sources. Thus, proper radiation source verification is paramount to ensure patient safety and treatment effectiveness